Microbocenoses of permafrost forest soils in Central Yakutia - N. P. Kuz’mina; S. V. Ermolaeva; A. P. Chevychelov (Сибирский лесной журнал, 2022)
For the first time a study of microbial communities of permafrost forest soils of the Yakut Botanical Garden of the Institute of Biological Problems of Cryolithozone, Russian Academy of Sciences, Siberian branch was conducted. The studied area is characterized by high soil diversity, almost all types of forest soils found in Central Yakutia are common here. It was found that in the studied permafrost soils in 2019, the number of cultivated microorganisms ranged from 5.2 ± 0.5 × 102 to 2.5 ± 0.1 × 106 CFU/g of soil. Humus-carbonate soil turned out to be the most saturated with microorganisms of all types of permafrost soils, and malt was the poorest. According to the total number of microorganisms, humus-carbonate and pale gray soils formed as a result of the turf soil formation process were distinguished. It was noted that microorganisms were concentrated in the upper organogenic horizons and their number decreased with depth. Mycelial microorganisms dominated in the microbocenoses of the studied four out of five types of soils formed on loose light alluvial deposits, and ammonifying bacteria prevailed in the microbocenoses of malt developing on loess-like alluvial loams. It was found that the predominance of certain groups of microorganisms depended on the chemical composition of soils, as well as on the characteristics of their formation. Mycelial fungi were mainly represented by representatives of the genera Aspergillus sp. and Penicillium sp. Aerobic cellulolytic microorganisms were found in the amount of 5.2 ± 0.5 × 102 – 8.3 ± 4.1 × 104 CFU/g, most of them were found in humus-carbonate soil. Nitrogen fixators were found only in humus-carbonate soil (98 %). It has been studied that the number of microorganisms with physicochemical parameters (C, N, pH, humidity) correlates in different types of soils in different ways. The change in the number of microorganisms mainly depended on the soil temperature, humus and nitrogen content.